Science project ideas about the sun - Gardner, Robert, 1929-; Katari, Jacob (Berkeley Heights, NJ : Enslow, 1997)
Uses experiments to illustrate the phases and patterns of the sun as well as the reasons for its importance as an energy source.
Includes bibliographical references (p. 94) and index.
Book Report.
School Library Journal.
Wilson's Junior High School.
4.8.
4.8
Keywords: Experiments; Experiments; Sun -- Experiments -- Juvenile literature; Sun -- Experiments; Sun -- Experiments